Fabrication of antifouling membranes by blending poly(vinylidene fluoride) with cationic polyionic liquid. Issue 29 (26th December 2019) - Shen, Shusu; Zhang, Linbin; Zhang, Yiyuan; Zhang, Ganwei; Yang, Jingjing; Bai, Renbi
ABSTRACT: Membrane fouling problem is now limiting the rapid development of membrane technology. A newly synthesized cationic polyionic liquid (PIL) [P(PEGMA‐ co ‐BVIm‐Br)] was blended with poly(vinylidene fluoride) (PVDF) to prepare antifouling PVDF membranes. The PVDF/P(PEGMA‐ co ‐BVIm‐Br) exhibited an increased surface hydrophilicity, the water contact angle was reduced from 77.8° (pristine PVDF) to 57.9°. More porous membrane structure was obtained by adding PIL into the blending polymers, as high as 478.0 L/m 2 ·h of pure water flux was detected for the blend PVDF membrane in comparison with pristine PVDF (17.2 L/m 2 ·h). Blending of the cationic PIL with PVDF gave a more positive surface charge than pristine PVDF membrane. Blend membranes showed very high rejection rate (99.1%) and flux recovery rate (FRR, 83.0%) to the positive bovine serum albumin (BSA), due to the electrostatic repulsion between the membrane surface and proteins. After three repeated filtration cycles of positive BSA, the blend PVDF membranes demonstrated excellent antifouling performance, the permeation flux of the membranes was recovered very well after a simple deionized water washing, and as high as 70% of FRR was obtained, the water flux was maintained at above 350 L/m 2 ·h. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48878. Abstract :